Polymer-Laminated Ti3C2Tx MXene Electrodes for Transparent and Flexible Field-Driven Electronics - Lee, Seokyeong; Kim, Eui Hyuk; Yu, Seunggun; Kim, Hyerim; Park, Chanho; Lee, Seung Won; Han, Hyowon; Jin, Wookyoung; Lee, Kyuho; Lee, Chang Eun; Jang, Jihye; Koo, Chong Min; et al. (AMER CHEMICAL SOC, 2021)
MXenes (Ti3C2Tx) are two-dimensional transition metal carbides and carbonitrides with high conductivity and optical transparency. However, transparent MXene electrodes with high environmental stability suitable for various flexible organic electronic devices have rarely been demonstrated. By laminating a thin polymer film onto a solution-processed MXene layer to protect the MXene film from harsh environmental conditions, we present transparent and flexible MXene electronic devices. A thin polymer layer spin-coated onto a transparent MXene electrode provides environmental stability even under air exposure longer than 7 d at high temperatures (up to 70 degrees C) and humidity levels (up to 50%) without degrading the transparency of the electrode. The resulting polymer-laminated (PL) MXene electrode facilitates the development of a variety of field-driven photoelectronic devices by exploiting the electric field exerted between the MXene layer and the counter electrode through the insulating polymer. Field-induced electroluminescent displays, based on both organic and inorganic phosphors, with PL-MXene electrodes are demonstrated with high transparency and mechanical flexibility. Furthermore, our PL-MXene electrode exhibits high versatility through successful implementation in capacitive-type pressure sensors and triboelectric nanogenerators, resulting in field-driven sensing and energy harvesting electronic devices with excellent operation reliability.
Keywords: LIGHT-EMITTING-DIODES; 2-DIMENSIONAL TI3C2; HIGHLY TRANSPARENT; LOW-TEMPERATURE; OXIDATION; FILMS; CARBON; COMPOSITE; SENSORS